Socio-economic context of soil erosion: A comparative local stakeholders' case study from traditional agricultural region in the Czech Republic. (May 2019) - Vávra, Jan; Duží, Barbora; Lapka, Miloslav; Cudlínová, Eva; Rikoon, J. Sanford
Highlights: Comparative research of soil erosion perceptions of farmers and local leaders. Over 75% of all stakeholders see soil erosion as a big problem. Irresponsible farmers are seen as the most important cause by all stakeholders. Growing appropriate crops is most preferred activity to mitigate the problem. Farmers tend to have more productivist views on agriculture than local leaders. Abstract: Soil erosion by water is the most common cause of land degradation and traditionally coincides with agricultural production. This paper presents the results of a sociological case study comparing the perceptions of soil erosion of stakeholder groups from southern Moravia, an intensive agricultural and erosion-prone region in the Czech Republic. The research documents and analyses perceptions of erosion, perceived causes, and attitudes towards possible corrective measures. Altogether, 216 stakeholders consisting of farmers and local leaders (mostly mayors and vice-mayors) took part in a questionnaire survey between the years of 2012–2015. The results show that the stakeholders as whole are in general aware of the seriousness of the problem and see irresponsible farmers, lack of organic fertilizers and climate change as the major causes. Overall most preferred erosion mitigation measures were the growing of appropriate crops and the splitting of large fields into smaller ones. The views of farmers and local leaders are compared and discussed within the framework of the changing roles of rural areas. A productivist paradigm and corresponding modulation of erosion is significantly more prevalent among farmers, although not the dominant viewpoint in this group. The socio-economic context of soil erosion and recent trends in Czech soil conservation policies are discussed and it is argued that the local stakeholders are supportive of pro-environmental measures despite a lack of effort on the governmental and legislation level.